Bacterial and Fungal Contamination in Three Brands of Cosmetic Marketed in Iraq - Huda J. Muhammed (College of Pharmacy University of Baghdad, 2017)
Cosmetic products must be safe for use by consumers , It is also regulated and required the legislation of countries all over the world .  In this study out of 80 cosmetic products analyzed and 32.5% were found to be contaminated .Products such as mascara, lip pencil and eye pencil were analyzed . The contaminants including bacteria such as Staphylococcus aureus , Staphylocoocus epidermidis , Pseudomonas aeruginosa , Escherichia coli and Klebsiella pneumonia   which were ranging  in number  from (103-104 ) C.F.U. /ml and fungi such as Penicillium spp. , Aspergillus fumigatus and Candida albicans which were ranging in number from (102-104) C.F.U /ml . The water and other nutrients present in cosmetic make them susceptible to microbial growth . Microorganisms detected in recent study considered as pathogenic to human. Key words :  Bacterial contamination , Fungal contamination,Cosmetics.